Environment Control using Forecasting Algorithm by Real Time Data Analysis for Automatic Cultivation System - Pakorn Juleang; S. Mitatha (My University, 2021)
A new automatic cultivation system was proposed using a forecasting algorithm for environmental control. Information used for the forecast was taken from real time data obtained by a wireless sensor system. The objective was the automation of suitable environmental cultivation methods. The proposed forecasting algorithm used historical data to predict future environmental control according to its goals. A real system was implemented and constructed to test the hypothesis. Results showed that the system had the required features. Environmental controls of the original system were compared with the proposed algorithm according to the created thresholds. The proposed forecasting algorithm controlled humidity in the soil at 98.26%, while the original system recorded do 69.33%, with humidity in the air controlled at 93.87% compared to the original system at 48.96%. This algorithm will be very useful to promote sustainable agriculture.
Keywords: Smart Agriculture and AI; Greenhouse Technology and Climate Control; Water Quality Monitoring Technologies